Avaliação do impacto de alterações bucais na qualidade de vida de portadores de insuficiência renal crônica - Leal, Paula Miliana (2019)
Introduction: Some oral alterations such as number of decayed and missing decayed teeth, may interfere with the quality of life of individuals with chronic renal failure. Objective: To compare changes in Oral Health-Related Quality of Life (OHRQoL) and Health Related Quality of Life (HRQoL) in patients undergoing hemodialysis at two moments. Methodology: This was a prospective cohort longitudinal study of 226 patients submitted to hemodialysis in two hospitals that were enrolled in the Unified Health System (SUS) in the city of Campina Grande-PB. The patients answered a socioeconomic, demographic and clinical questionnaire, were submitted to the intraoral physical examination, and then the interview was carried out in which the Oral Health Impact Profile (OHIP-14) and 36 - Item Short-Form Health Survey (SF-36). After 3 years the patients were contacted again to participate in the research. Statistical analysis considered a significance level of 5% and used the Wilcoxon test to compare OHIP-14 and SF-36 scores between T1 (baseline) and T2 (three years later). Results: At the end of the study follow-up period, there was a significant increase in OHIP-14 global scores (p <0.001), and in all domains, functional limitation (p <0.001), physical pain (p <0.001), discomfort. (p <0.001), physical disability (p = 0.004), psychological disability (p <0.001), social disability (p <0.001) and disability (p <0.001). From the SF-36 questionnaire score, a statistically significant reduction in functional capacity was identified (p <0.001), increased limitation by physical aspects (p = 0.003), decreased pain level (p = 0.024), increased vitality (p = 0.006), decreased social aspects (p = 0.001) and decreased limitations due to emotional aspects (p <0.001). Conclusion: Over time, there was a reduction in the OHRQoL of patients on hemodialysis. Worsening of the dimensions of HRQoL, functional capacity and limitation due to physical aspectes were also identified.